SOSIALISASI MENGENAI PENCEGAHAN STUNTING PADA ANAK KEPADA IBU DI NAGARI DUSUN TANGAH KABUPATEN SOLOK SELATAN - Saputra, Muhammad Rizki; Rahma Triyana; Ruhsyahadati, Ruhsyahadati; Nana Liana; Rifkind Malik; Roland Helmizar; Suharni, Suharni; Sri Wahyuni; Rosmaini, Rosmaini; Alif Dhuha; Kendall Malik (Nusantara Hasana Journal, 2025)
This community service activity was carried out to support the acceleration of stunting reduction in Nagari Dusun Tangah, Solok Selatan Regency. Stunting is a public health problem that affects physical growth, cognitive development, and long-term productivity. This condition is primarily caused by inadequate maternal nutrition during pregnancy, improper child-feeding practices, recurrent infections, and poor environmental sanitation. The activity involved 22 participants, consisting of pregnant women and mothers of children under five. The methods used included interactive lectures, discussions, demonstrations of locally sourced complementary feeding (MP-ASI), sanitation education, promotion of clean and healthy living behaviors, and basic training for posyandu cadres. Pre-test and post-test assessments were conducted to measure the increase in participants' knowledge. The results showed positive responses and strong interest among participants in improving child-feeding practices and household hygiene. The MP-ASI demonstration using local ingredients such as eggs, freshwater fish, and homegrown vegetables was considered highly beneficial. The increase in participants' knowledge aligns with theoretical causes of stunting, particularly related to optimal nutrition, infection prevention, and sanitation. This activity also strengthened the capacity of posyandu cadres and enhanced collaboration between the puskesmas, local government, and the community. Overall, the socialization successfully improved family understanding of stunting prevention and is expected to serve as an initial step toward sustainable community-based nutrition interventions.